Deindustrialization, "Premature" Deindustrialization, and "Dutch Disease"; [Desindustrialización, Desindustrialización "Prematura" y "Síndrome Holandés"] - Palma-Penco, J (Fondo de Cultura Economica, 2019)
The frustration in Latin America with neoliberal economic reforms has reawakened a number of debates, especially about inequality (Palma, 2019a) and producti-vity growth Palma (2019c) -in 2018, the region s average productivity was just 8% higher than in 1980, equivalent to an annual average growth rate of just 0.2%-. Meanwhile, in the previous cycle, from 1950 to 1980, productivity levels more than doubled, with an annual growth rate of 2.8%. One of these debates is related to the problem of deindustrialization -in particular, the question of whether it is "premature" or if it includes a component of "Dutch disease"-. This paper analyses the role of manufacturing in economic growth, and shows the dynamics of that deindustrialization in high-income as well as middle-income countries. It concludes that the success of emerging Asia is rooted in its ideological pragmatism, which led it in the 1980s and early 1990s to use reforms as a mechanism for strengthening and accelerating their already ambitious processes of industrialization -not for carrying out a "non-creative destruction" of their manufacturing, as happened in almost all of Latin America-. This in spite of the fact that many of the industrialization processes in emerging Asia suffered, in its time, from similar problems to those experienced by Latin American industrialization, if not worse. © 2019 Fondo de Cultura Economica. All rights reserved.